Identificamos información implícita en un texto descriptivo - Salinas Blas, Azucena Marilú (2020)
This teaching proficiency piece of work involves the planning, implementation and theoretical support of the Learning Session entitled: “Identifying implicit information in a descriptive text” which aims to set the importance of reading comprehension as a social experience and is intended to fourth grade primary school boys and girls from the Educational Institution “Juan Pablo II” in Trujillo city, in 2019 Reading comprehension is considered the basic skill not only for theoretical learning but for developing essential communication skills that allow students to play a proper role within a globalized world with high standards of competitiveness. Furthermore, it promotes the practice of ethical principles as well as improving remembrance and creativity skills. _x000D_ Our main goal is to achieve the learners’s acquisition of different levels of reading comprehension strategies in order to identify implicit information in a written text and promote meaningful learning. The strategies that have been planned for this learning session, seek to elicit the interest in reading, since the Communication area encourages students to learn how to read and understand different kinds of texts according to the in various contexts in which they perform.